Deregulation of MicroRNAs in Gastric Lymphomagenesis Induced in the d3Tx Mouse Model of Helicobacter pylori Infection - Floch, Pauline; Capdevielle, Caroline; Staedel, Cathy; Izotte, Julien; Sifré, Elodie; Laur, Amandine M.; Giese, Alban; Korolik, Victoria; Dubus, Pierre; Mégraud, Francis; Lehours, Philippe (Frontiers in Cellular and Infection Microbiology, 2017)
Helicobacter pylori infection is considered as an excellent model of chronic inflammation-induced tumor development. Our project focuses on gastric MALT lymphoma (GML) related to H. pylori infection and mediated by the chronic inflammatory process initiated by the infection. Recently, microRNAs (miRNAs) have emerged as a new class of gene regulators, which play key roles in inflammation and carcinogenesis acting as oncogenes or tumor suppressors. Their precise characterization in the development of inflammation and their contribution in regulating host cells responses to infection by H. pylori have been little explored. Our goal was to analyze the changes in miRNAs in a GML mouse model using BALB/c mice thymectomized at day 3 post-birth (d3Tx model) and to clarify their implication in GML pathogenesis. PCR array followed by RT-qPCR identified five miRNAs (miR-21a, miR-135b, miR-142a, miR-150, miR-155) overexpressed in the stomachs of GML-developing d3Tx mice infected by H. pylori. The analysis of their putative targets allowed us to identify TP53INP1, an anti-proliferative and pro-apoptotic protein, as a common target of 4 of the 5 up-regulated miRNAs. We postulate that these miRNAs may act in synergy to promote the development of GML. miR-142a was also overexpressed in mouse sera samples and therefore could serve as a diagnostic marker. In situ hybridization on gastric samples with miR-142a revealed a global up-regulation of this miRNA by the tumor microenvironment at the lymphoma stage. Dysregulation of miR-21a, miR-135b, miR-142a, miR-150, miR-155could play a critical role in the pathogenesis of GML and might offer potential applications as therapeutic targets and novel biomarkers for this disease.